LINGUISTIC STRATEGIES USED FOR THE SPEECH ACT OF RESPONDING TO ADMONISHMENT OF DIFFERENT SEX, SOCIAL STATUS AND INTIMACY INTERLOCUTORS IN THAI - Ongwuttiwat, Sittitam (RMUTK Journal of Liberal Arts, 2021)
This research article had the primary objectives to 1) study the strategies used for the speech act of responding to admonishment in Thai and 2) analyze the relationship between responding strategies and factors concerning the sex of speakers and interlocutors’ social status and intimacy. Data used in this research were elicited from samples of 400 respondents, of which 200 were male and 200 were female. The samples were asked to complete the Written Discourse Completion Task (WDCT). According to the results, the responding strategy to admonishment was divided into 2 strategies, ranking in the order of frequency as follows: 1) keeping relationship of interlocutor linguistic strategies (84.39%) and 2) conflicting linguistic strategies (15.61%). Upon consideration of the relationship between responding strategies and factors concerning the sex of speakers and interlocutors’ social status and intimacy, it was evident that factors concerning the sex of speakers interlocutors’ social status and intimacy had an effect on the adoption of the responding strategies. There were statistically significant differences in the responding strategies at a p-value of less than .05 (p<0.05).